Pengaruh Profitabilitas, Kebijakan Dividen, Ukuran Perusahaan dan Likuiditas Terhadap Nilai Perusahaan Pada Sektor Pertambangan - Maharani, Nabila Putri; animah, animah; Sukma, Paradisa (Akbis: Media Riset Akuntansi dan Bisnis, 2025)
This study aims to analyze the influence of profitability, dividend policy, firm size, and liquidity on firm value in mining companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative approach with panel data regression. The sample consists of mining companies listed on the IDX from the 2019–2023 period, selected using a purposive sampling method. Firm value is proxied by Price to Book Value (PBV), profitability by Return on Assets (ROA), dividend policy by Dividend Payout Ratio (DPR), firm size by Ln Total Assets, and liquidity by the Current Ratio (CR). Data analysis was conducted using EViews with classical assumption tests, the F-test, and the t-test. The results indicate that profitability and dividend policy have a significant positive influence on firm value. Meanwhile, firm size also has a positive influence but it is not significant. Conversely, liquidity has a negative and insignificant influence on firm value. This study is limited to mining companies listed on the IDX during the 2019–2023 period; therefore, the results may not be generalizable to other sectors. Future research could extend the observation period, make comparisons across industries, or add other variables not covered in this research model.